A foresight study on nanotechnology in cosmetics industries in Malaysia - Ramasamy, Chandrashekar; Hsin, Chan Yuet; Shamsuddin, Alina (American Scientific Publishers, 2018)
The advancement of science and technology has greatly impacted the society because these scientific advances and technological elements are the key performances to improve competitive advantage and enhance the nation’s economic status. Recent years, there are an increasing emphasis on nanotechnology because nanotechnology is becoming popular and it is seen as a potential technology to replace the existing limitations with current conventional computer hardware lithography capabilities and it would be a new generation of technology that is more environmental friendly, reliable and precise to society. The current study aims to identify the issues and drives of employing nanotechnology in cosmetic industries and to study the future trend of nanocosmetics in Malaysia. STEEPV approach which is an acronym for (Social, Technological, Environmental, Economic, Political and Values) is an internationally recognized tool used in conducting Technology Foresight worldwide. This tool was used in the current research in identifying various issues and drives falling under the above mentioned six categories. Need an efficient waste management system and usage of biocompatible and biodegradable compounds in nanocosmetics was voted as the most influential drivers for the nanocosmetics industries in Malaysia. In line with this regard, a scenario development was done and a number of solution were suggested in order to move towards sustainable development of nanocosmetics industry. As a consequence it is recommended to add more political will and support in such solution to ensure the ownership at the top level and maximize the chances of implementing the outcomes.